Measurement of physical activity and physical fitness in preschool children - Međedović Bojan; Osmankać Nedžad; Dimitrić Ivan; Pantović Marko; Nedeljkov Nebojša; Grujičić Dragan (University Educons, Faculty of Sports and Tourism, Novi Sad, 2014)
Physical activity has been positively associated with reduction of risk of cardiovascular disease, obesity, diabetes, pulmonary disease, etc. Although much of the research related to physical activity has been conducted with adults, data related to the activity levels and fitness status of children appear to be as alarming. From 1990 until today, there has been a downward trend in the amount of physical activity in children of all age groups. One major problem in conducting research related to physical activity in children is the absence of accurate and reliable measures of physical activity. When we look at the majority of the used test batteries, we can notice that all of them measure the same components: cardiorespiratory fitness, muscle fitness, flexibility, and body composition. On the other hand, one of the most common types of measurement of physical activity is self-report. The aim of the research is to determine the level of components of physical fitness of preschool children using the recommended testing procedure and evaluation of leisure physical activity with self-report. This research provides information about physical fitness of preschool children and the relation between the volume of leisure time physical activity and physical fitness. Results indicate that children, even at this age, show poor condition of some components of physical fitness related to health. In addition to that, it was established that children were not sufficiently physically active in daily and weekly sport and recreational activities.